Precision of Corneal Thickness Measurements Obtained Using the Scheimpflug-Placido Imaging and Agreement with Ultrasound Pachymetry. (24th February 2015) - Huang, Jinhai; Savini, Giacomo; Wang, Chengfang; Lu, Weicong; Gao, Rongrong; Li, Yuanguang; Wang, Qinmei; Zhao, Yune
Abstract : Purpose. To assess the reliability and comparability of measuring central corneal thickness (CCT) and thinnest corneal thickness (TCT) using a new Scheimpflug-Placido analyzer (TMS-5, Japan) and ultrasound (US) pachymetry. Methods. Seventy-six healthy subjects were prospectively measured 3 times by 1 operator using the TMS-5, 3 additional consecutive scans were performed by a second operator, and ultrasound (US) pachymetry measurements were taken. The test-retest repeatability (TRT), coefficient of variation (CoV), and intraclass correlation coefficient (ICC) were calculated to evaluate intraoperator repeatability and interoperator reproducibility. Agreement among the devices was assessed using Bland-Altman plots and 95% limits of agreement (LoA). Results. The intraoperators TRT and CoV were <19  μ m and 2.0%, respectively. The interoperators TRT and CoV were <12  μ m and 1.0%, respectively, and ICC was >0.90. The mean CCT and TCT measurements using the TMS-5 were 15.97  μ m (95% LoA from −26.42 to −5.52  μ m) and 20.32  μ m (95% LoA from −30.67 to −9.97  μ m) smaller, respectively, than those using US pachymetry. Conclusions. The TMS-5 shows good repeatability and reproducibility for measuring CCT and TCT in normal subjects but only moderate agreement with US pachymetry results. Caution is warranted before using these techniques interchangeably.